Integrasi Kecerdasan Buatan AI dalam Pembelajaran Sebagai Strategi Penumbuhan Technopreneurship Peserta Didik di MAN 1 Pamekasan - Firnanda, Aldi; Dwijayanti , Novia Shafa; Hamdani, Sahril; Siddik, Achmad Muafi; Mukarromah, Lutviatul (Islamic Education Management Study Program, Tarbiyah and Teacher Training Faculty, State Islamic University of Madura, 2026)
The integration of artificial intelligence in learning at MAN 1 Pamekasan still faces conceptual and pedagogical challenges in directing its utilization to foster creative, innovative, and technopreneurial attitudes in students. This research aims to analyze the forms of artificial intelligence integration in learning and its role in fostering technopreneurship among students at MAN 1 Pamekasan. This research uses a field-based qualitative method. Research data was obtained thru interviews, observations, and documentation. The research findings indicate that artificial intelligence has been integrated into learning as a learning aid, a source for exploring ideas, a means for project development, and a support for learning evaluation. Some of the artificial intelligence used include ChatGPT, Canva, Gemini AI, and Google Classroom. The utilization of artificial intelligence contributes to encouraging students to think creatively, innovatively, and adaptively, especially in designing simple digital products and simulating technology-based business opportunities. The integration of artificial intelligence still faces obstacles such as infrastructure intelligence, the digital literacy gap, and the need to strengthen technology in learning. This research is expected to contribute to artificial intelligence-based learning that focuses on strengthening technopreneurship in secondary education.